Енергоефективні та енергозберігаючі технології на транспорті - Гнатов, Андрій; Ульянець, Ольга; Аргун, Щасяна (Видавництво Львівської політехніки, 2018)
The analysis of author's developments in the field of energy-efficient and energy-saving technologies on transport has been carried out. We proposed for implementation and realization: ultracapacitor electrobus with superfast charging for urban transport; multifunctional panels of pavement; Electrical energy generation device - the energy generation slabb.
Energy efficiency and energy saving technologies on transportation
Keywords: 624.318